Support of the Laboratory in the Diagnosis of Fungal Ocular Infections - Virginia Vanzzini Zago; Marino Alcantara Castro; Ramon Naranjo Tackman (International Journal of Inflammation)
This is a retrospective, and descriptive study about the support that the laboratory of microbiology aids can provide in the diagnosis of ocular infections in patients whom were attended a tertiary-care hospital in México City in a 10-year-time period. We describe the microbiological diagnosis in palpebral mycose; in keratitis caused by Fusarium, Aspergillus, Candida, and melanized fungi; endophthalmitis; one Histoplasma scleritis and one mucormycosis. Nowadays, ocular fungal infections are more often diagnosed, because there is more clinical suspicion and there are easy laboratory confirmations. Correct diagnosis is important because an early medical treatment gives a better prognosis for visual acuity. In some cases, fungal infections are misdiagnosed and the antifungal treatment is delayed.